Criminal Psychology and its importance : A Review - Singh, Dr. Dinesh (Innovative Research Thoughts, 2018)
Criminal psychologists seek to understand the motivations of criminals and develop a psychological profile to understand or apprehend them. They examine individual criminal behaviors and diagnose any mental health conditions. They frequently step into the courtroom to provide expert testimony. Other duties include counseling individuals who have committed crimes or evaluating their risk of recidivism. Becoming a criminal psychologist requires a doctorate in psychology and a license to practice. These professionals have usually completed postdoctoral study or research in criminal behavior or profiling. Criminal psychologists often come from a law enforcement background, bringing skills learned in the field to graduate programs, where they refine their psychological profiling abilities. There are many other positions in this field, however, and many who study criminal psychology go on to work in social service or in a field related to law enforcement, often as corrections and probation officers, or as police, fire, emergency, and ambulance dispatchers.